A Employment Development Survey of NPC Swimming Atlets in Surakarta 2018 - Batitusta, Muhammad Rizki; Supriyono, Supriyono (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2019)
The purpose of this study was to determine the organizational system, coaching accomplishments, exercise programs, achievements, sources of funds, completeness and swimming sports infrastructure conditions the National Paralympic Committee of Indonesia in Surakarta 2018. The research approach used is qualitative descriptive approach. Research data collection techniques using the method of observation, interviews, and documentation. The validity of the data in this study using data triangulation. Technical analysis of the data include: data collection, data reduction, data presentation, and conclusion data. The results showed that the NPC Board running the organization in accordance with the duties and responsibilities. Coaching accomplishments done through three stages namely; pemassalan stage, seedling stage, and the stage of development achievements. The exercise program sports such as swimming in NPC training schedules, workout intensity, periodization, physical exercises, techniques, and tactics. Through this achievement coaching athletes with disabilities have an outdoor sport sporting achievement increased from year to year. NPC obtain funding from Kemenpora. The Fund is managed by a NPC to run coaching. Completeness and condition of the infrastructure used for swimming practice is quite good and sufficient. NPC coaching swimming athlete’s performance goes well, ranging from performance management, the coach up to the achievements of athletes in national and international competitions.